1997
DOI: 10.1007/bf02552193
|View full text |Cite
|
Sign up to set email alerts
|

The necessity of prophylactic antibiotics during extracorporeal shock wave lithotripsy

Abstract: In this study we treated 340 patients with renal and ureteric stones. They all underwent ESWL with the HM-4 lithotriptor. The patients were divided into two groups, the first one including 250 patients and the second 90. The first group consisted of patients with sterile urine prior to ESWL. These patients did not receive any antibiotic prophylaxis, while 5.2% of them developed infectious problems which were followed by significant bacteriuria in only 2% of the cases. The 90 patients of the second group had ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
0
5
0
4
Order By: Relevance
“…Die statistische Auswertung erfolgte mittels Mann-Whitney-Test, ein P-Wert < 0,05 wurde als statistisch signifikant gewertet. [10,11]. Im Rahmen der hochenergetischen Stoûwellentherapie zur Behandlung infizierter Pseudarthrosen konnte dies allerdings bislang nicht beobachtet werden [15].…”
Section: Materials Und Methodenunclassified
“…Die statistische Auswertung erfolgte mittels Mann-Whitney-Test, ein P-Wert < 0,05 wurde als statistisch signifikant gewertet. [10,11]. Im Rahmen der hochenergetischen Stoûwellentherapie zur Behandlung infizierter Pseudarthrosen konnte dies allerdings bislang nicht beobachtet werden [15].…”
Section: Materials Und Methodenunclassified
“…(2) Incidence of perioperative infections in ESWL [127][128][129][130][131][132][133][134][135][136][137][138][139] The incidences of asymptomatic bacteriuria and symptomatic UTIs after ESWL without preoperative bacteriuria were approximately 10% (ranging from 0 to 24%) and 3% (ranging from 0 to 10%), resp ectively. In addition, the incidence of bacteremia was 0-7.7%, most of which were suspected skin contamination.…”
Section: Ii-ix Extracorporeal Shock Wave Lithotripsy (Eswl) (1) Pecumentioning
confidence: 99%
“…In a few follow-up studies, the frequency of post-ESWL bacteriuria has been shown to be ≤5% in patients without known risk factors [47][48][49]. In only one [50] of five randomized placebo/non-antibiotic-controlled studies was a significant reduction demonstrated [50][51][52][53][54].…”
Section: Extracorporeal Shock-wave Lithotripsy (Eswl)mentioning
confidence: 95%